2015
DOI: 10.1080/14399776.2015.1006979
|View full text |Cite
|
Sign up to set email alerts
|

Axial piston pumps slippers with nanocoated surfaces to reduce friction

Abstract: This paper shows the experimental results obtained using a nanocoating (developed by ISTEC-C.N.R.) applied to the slippers of an axial piston pump to reduce the friction losses in order to improve the pump overall efficiency map. It is well known that the mechanical power losses in a hydraulic pump come from the friction between parts in relative motion. The need to provide, especially at low rotational speed, hydrodynamic lift causes power losses in terms of volumetric and mechanical efficiency, due to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…According to the Č ornˇa´k, 29 contamination of the hydraulic fluid results in accelerated wear of the individual hydraulic elements of the whole hydraulic system, as well as corrosion of steel surface, oxidation of the fluid and change in its physical and chemical properties. The Dobrota et al 30 and Rizzo et al 31 dealt with the efficiency of the hydraulic pumps in their articles. In his article, the Dobrota et al 30 found the efficiency of the hydraulic pump at value 95%, while the Rizzo et al 31 in his work states the efficiency of the hydraulic pump 92%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Č ornˇa´k, 29 contamination of the hydraulic fluid results in accelerated wear of the individual hydraulic elements of the whole hydraulic system, as well as corrosion of steel surface, oxidation of the fluid and change in its physical and chemical properties. The Dobrota et al 30 and Rizzo et al 31 dealt with the efficiency of the hydraulic pumps in their articles. In his article, the Dobrota et al 30 found the efficiency of the hydraulic pump at value 95%, while the Rizzo et al 31 in his work states the efficiency of the hydraulic pump 92%.…”
Section: Resultsmentioning
confidence: 99%
“…The Dobrota et al 30 and Rizzo et al 31 dealt with the efficiency of the hydraulic pumps in their articles. In his article, the Dobrota et al 30 found the efficiency of the hydraulic pump at value 95%, while the Rizzo et al 31 in his work states the efficiency of the hydraulic pump 92%. In the measurements made in the present article under laboratory conditions, we recorded the efficiency of the hydraulic pump after working 500 h at the level of 92.05%.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the new superhydrophobic and oleophobic surface on the hydrostatic lubrication was investigated thanks to a dedicated test rig. The results [29][30][31] showed that, using the functionalized oleophobic coating, is possible to have a friction coefficient reduction from 20 to 30%, in function of the different working condition.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Their results indicate that the slipper boot temperature is mainly affected by the input heat flux and the heat conduction. To date, most studies have focused on the thermal characteristics and friction performance of slipper pairs under oil film lubricating conditions [4,12]. Although the effects of the physical property parameters of a friction pair on the temperature field of the friction surfaces under dry friction conditions have not been discussed, these parameters have a significant influence on the temperature increase of the friction surfaces and affect the bearing capacity of the slipper pairs.…”
Section: Introductionmentioning
confidence: 99%